구형렌즈를 적용한 CPV 모듈 발전성능 분석에 관한 연구 - 정병호(Byeong-Ho Jeong); 김남오(Nam-Oh Kim); 이강연(Kang-Yoen Lee) (전기학회 논문지 P권, 59(3), 2010)
Next generation concentrating photovoltaic technologies could have a large-scale impact on world electricity production once they will become economically attractive and grid parity will be reached. Multi-junction solar cells will be characterised by a high value of the cell economical performance index if the cells were able to operate at high concentration level. Concentrating the sunlight by optical devices like lenses or mirrors reduces the area of expensive solar cells or modules, and, moreover, increases their efficiency. Accurate and reliable tracking is an important issue to maintain high the CPV system output power. Further, for high concentration CPV systems, the actual tracker cost is about 20% of the total CPV system cost. In this paper high-concentration is defined as systems using concentration ratios well above 100 times the one sun intensity and trackerlss CPV system studied. Using sphericalness lens and parallel MJ cell connection method were suggested and achieved experiment on a clear day in summer. Development of these high performance multi-junction CPV module promises to accelerate growth in photovoltaic power generation.